Contribution of chronic conditions to disability in men and women in France. (9th August 2018) - Nusselder, Wilma J; Wapperom, Dagmar; Looman, Caspar W N; Yokota, Renata T C; van Oyen, Herman; Jagger, Carol; Robine, Jean Marie; Cambois, Emanuelle M
Abstract: Background: Women report more disability than men perhaps due to gender differences in the prevalence of diseases and/or in their disabling impact. We compare the contribution of chronic diseases to disability in men and women in France, using a disability survey conducted in both private households and institutions, and we also examine the effect of excluding the institutionalized population. Methods: Data comprised 17 549 individuals age 50+, who participated in the 2008–09 French Disability Health Survey including people living in institutions. Disability was defined by limitations in activities people usually do due to health problems (global activity limitation indicator). Additive regression models were fitted separately by gender to estimate the contribution of conditions to disability taking into account multi-morbidity. Results: Musculoskeletal diseases caused most disability for both men (10.1%, CI: 8.1–12.0) and women (16.0%, CI 13.6–18.2). The second contributor for men was heart diseases (5.7%, CI: 4.5–6.9%), and for women anxiety-depression (4.0, CI 3.1–5.0%) closely followed by heart diseases (3.8%, CI 2.9–4.7%). Women's higher contribution of musculoskeletal diseases reflected their higher prevalence and disabling impact; women's higher contribution of anxiety-depression and lower contributions of heart diseases reflected gender differences in prevalence. Excluding the institutionalized population did not change the overall conclusions. Conclusions: The largest contributors to the higher disability of women than men are moderately disabling conditions with a high prevalence. Whereas traditional disabling conditions such as musculoskeletal diseases are more prevalent and disabling in women, fatal diseases such as cardiovascular disease are also important contributors in women and men.